THE IMAGE OF BERUNI IN THE NOVEL “IBN SINO” BY MAKSUD QORIEV - Anvar Allambergenov (Journals Park Publishing, 2022)
The article analyzes the interpretation of the episodic image of Beruni in the novel by Maksud Koriev “Ibn Sino”. Despite the fact that the image of Beruni in the novel is episodic, the author managed to reveal, within the limits of the novel's capabilities, his characteristic features as a historical personality and a great scientist.
Keywords: episodic image, author's language, character language, historical period, historical truth, artistic skill.